Apixaban for Stroke Prevention in Subclinical Atrial Fibrillation - Healey, Jeff S; Lopes, Renato D; Granger, Christopher B; Alings, Marco; Rivard, Lena; McIntyre, William F; Atar, Dan; Birnie, David H; Boriani, Giuseppe; Camm, A John; Conen, David; Erath, Julia W; et al. (The New England journal of medicine, 2024)
BACKGROUND: Subclinical atrial fibrillation is short-lasting and asymptomatic and can usually be detected only by long-term continuous monitoring with pacemakers or defibrillators. Subclinical atrial fibrillation is associated with an increased risk of stroke by a factor of 2.5; however, treatment with oral anticoagulation is of uncertain benefit. METHODS: We conducted a trial involving patients with subclinical atrial fibrillation lasting 6 minutes to 24 hours. Patients were randomly assigned in a double-blind, double-dummy design to receive apixaban at a dose of 5 mg twice daily (2.5 mg twice daily when indicated) or aspirin at a dose of 81 mg daily. The trial medication was discontinued and anticoagulation started if subclinical atrial fibrillation lasting more than 24 hours or clinical atrial fibrillation developed. The primary efficacy outcome, stroke or systemic embolism, was assessed in the intention-to-treat population (all the patients who had undergone randomization); the primary safety outcome, major bleeding, was assessed in the on-treatment population (all the patients who had undergone randomization and received at least one dose of the assigned trial drug, with follow-up censored 5 days after permanent discontinuation of trial medication for any reason). RESULTS: We included 4012 patients with a mean (±SD) age of 76.8±7.6 years and a mean CHA2DS2-VASc score of 3.9±1.1 (scores range from 0 to 9, with higher scores indicating a higher risk of stroke); 36.1% of the patients were women. After a mean follow-up of 3.5±1.8 years, stroke or systemic embolism occurred in 55 patients in the apixaban group (0.78% per patient-year) and in 86 patients in the aspirin group (1.24% per patient-year) (hazard ratio, 0.63; 95% confidence interval [CI], 0.45 to 0.88; P = 0.007). In the on-treatment population, the rate of major bleeding was 1.71% per patient-year in the apixaban group and 0.94% per patient-year in the aspirin group (hazard ratio, 1.80; 95% CI, 1.26 to 2.57; P = 0.001). Fatal bleeding occurred in 5 patients in the apixaban group and 8 patients in the aspirin group. CONCLUSIONS: Among patients with subclinical atrial fibrillation, apixaban resulted in a lower risk of stroke or systemic embolism than aspirin but a higher risk of major bleeding. (Funded by the Canadian Institutes of Health Research and others; ARTESIA ClinicalTrials.gov number, NCT01938248.).
Keywords: senioři; dvojitá slepá metoda; Embolism; Stroke; senioři nad 80 let; Double-Blind Method; Canada; lidé; výsledek terapie; mužské pohlaví; krvácení; Factor Xa Inhibitors; cévní mozková příhoda; Aged, 80 and over; antikoagulancia; Pyridones; ženské pohlaví; Humans; Anticoagulants; Aspirin; fibrilace síní; pyridony; inhibitory faktoru Xa; Hemorrhage; Female; Aged; Atrial Fibrillation; Treatment Outcome; embolie; Kanada; Male